2020
DOI: 10.3389/fimmu.2020.01949
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Immune Response During SARS-CoV-2 Infection: Lessons From the Past

Abstract: After the 1918 flu pandemic, the world is again facing a similar situation. However, the advancement in medical science has made it possible to identify that the novel infectious agent is from the coronavirus family. Rapid genome sequencing by various groups helped in identifying the structure and function of the virus, its immunogenicity in diverse populations, and potential preventive measures. Coronavirus attacks the respiratory system, causing pneumonia and lymphopenia in infected individuals. Viral compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
361
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(390 citation statements)
references
References 198 publications
(204 reference statements)
3
361
0
2
Order By: Relevance
“…One explanation could be that the adaptive immune response of these patients was still early and IgG titers were still very low. Alternatively, innate immunity could have played a role in defense against the SARS-CoV-2 infection in these patients [ 16 , 17 ]. In addition, a few control patients displayed an IgG response to the SARS-CoV-2 N proteins, suggesting that there might be some reactivity with other coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation could be that the adaptive immune response of these patients was still early and IgG titers were still very low. Alternatively, innate immunity could have played a role in defense against the SARS-CoV-2 infection in these patients [ 16 , 17 ]. In addition, a few control patients displayed an IgG response to the SARS-CoV-2 N proteins, suggesting that there might be some reactivity with other coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Simply reviewing what is known of the immunological function of the top two over- and top two under-expressed genes ranked by Hedges' g ES contextualizes ACO1 and ATL3 further with hints of a battle of host versus “novel” pathogen, never encountered by the immune system before. The impact on the function of host immune cells during SARS-CoV-1 and MERS infection is driven by their non-structural proteins and affects the normal production of cytokines compared to that of currently circulating viral infections, such as the repression of interferon proteins/ interferons (IFNs) ( Hu et al., 2012 ; Shah et al., 2020 ). Recently, Blanco-Melo et al.…”
Section: Discussionmentioning
confidence: 99%
“…21 SARS-CoV-2 infects ACE2-expressing cells in the lungs such as type 2 alveolar cells, leading to the dampening of antiviral IFN responses, while the infiltration of adaptive immune cells in the lungs can lead to heightened inflammatory responses resulting in pulmonary oedema. 22 Innate immune responses against SARS-CoV-2 are initially prompted by lung epithelial cells, alveolar macrophages and neutrophils, which then trigger adaptive immune responses involving T and B lymphocytes. 16 Ex vivo models showed that SARS-CoV-2-infected pneumocytes and alveolar macrophages prompted the release of proinflammatory cytokines and antiviral IFN (type I and III) at low levels.…”
Section: Immune Cells In the Lungs Of Sars-cov-2-infected Patientsmentioning
confidence: 99%